Investigation of Scale Effects on Linear Vertical Maneuvering Derivatives of a Submarine - Kahramanoglu, Emre; Sezen, Savas; Cakici, Ferdi (GALENOS PUBL HOUSE, 2024)
This paper aims to show the scale effects of vertical maneuvering derivatives for an underwater vehicle using computational fluid dynamics (CFD). The model scale and full-scale benchmark DARPA suboff hull forms were used in numerical vertical planar motion mechanism simulations to achieve this aim. The heave forces, pitch moments, and Euler coefficients are calculated together with the linear vertical maneuvering derivatives by implementing the Fourier series expansion approach. The results show that the coupled added mass terms are significantly influenced by the scale effects, whereas the impact of scale effects on the decoupled added mass and coupled and decoupled damping terms is negligible. Considering that the effects of the coupled added mass on the vertical maneuvering characteristics are almost negligible, the vertical maneuvering of a submarine is slightly influenced by the scale effects.
Keywords: Submarine; Vertical maneuvering derivatives; Scale effect; CFD; COMPREHENSIVE APPROACH; NUMERICAL PREDICTION; SURFACE COMBATANT; CFD SIMULATIONS; DARPA SUBOFF; VERIFICATION; VALIDATION; PROPULSION; Engineering; Transportation